2015
DOI: 10.1111/echo.12926
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Annular Plane Systolic Excursion and Its Association with Mortality in Critically Ill Patients

Abstract: Right ventricular systolic function, as assessed by TAPSE, has important prognostic value in critically ill patients. Mean values were lower in patients who died in-hospital versus those who survived to discharge. In addition, patients with TAPSE <2.4 cm had a longer hospital length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…Notably, patients with TAPSE < 16 mm showed a higher mortality rate when compared to those with TAPSE > 16 mm, a trend which did not reach statistical significance probably due to the small number of patients. However, our results are in keeping with those by Gajanana et al . who documented that TAPSE, as an index of RV systolic function, has an important prognostic value in critically ill patients.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, patients with TAPSE < 16 mm showed a higher mortality rate when compared to those with TAPSE > 16 mm, a trend which did not reach statistical significance probably due to the small number of patients. However, our results are in keeping with those by Gajanana et al . who documented that TAPSE, as an index of RV systolic function, has an important prognostic value in critically ill patients.…”
Section: Discussionsupporting
confidence: 93%
“…E/e’ was greater in non-survivors than survivors (15.32 ± 2.74 vs 9.05 ± 2.75, respectively; p = 0.0002) Lanspa et al (2016) [ 60 ] Single-center prospective cohort study/ICU 167 To compare the feasibility and prognostic significance of a simplified definition of diastolic dysfunction (using e’ and E/e’) with 2009 ASE guidelines. Primary outcome was 28-day mortality Simplified definition had better feasibility (87 vs 35%); similar clinical outcomes between groups suggesting limited utility of LAVI and DT in this setting Right ventricle Systolic TAPSE Gajanana et al (2015) [ 64 ] Single-center prospective cohort study/ICU 120 To evaluate the prognostic value of TAPSE in patients with critical illness A reduced TAPSE measurement (< 2.4 cm) was correlated with increased in-hospital mortality (χ(2) = 4.6, P = 0.03) and a longer length of hospital stay TAPSE TDI RV FAC Vallabhajosyula et al (2017) [ 67 ] Single-center retrospective cohort study/ICU 388 To evaluate the prognostic significance RV dysfunction in patients with severe sepsis and septic shock. Primary outcome was 1-year survival Isolated RV dysfunction is an independent predictor of 1-year survival (HR 1.6; p = 0.002).…”
Section: Pathophysiologymentioning
confidence: 99%
“…TAPSE is one of the most feasible and reproducible parameters that can reflect RV systolic function and has important prognostic value in critically ill patients. 4,21,22 MAPSE is a parameter found to be a highly accurate predictor of LV EF even by an untrained observer. 23 We also found that VTI is doi:10.24920/003685 much easier to acquire than LVEF.…”
Section: Discussionmentioning
confidence: 99%